Pengaruh Gaya Kepemimpinan Terhadap Kinerja Koperasi Karyawan PT. Semen Bosowa Maros - Muhammad Nurjaya; Tasmin Tanggareng; Adi Nawir; Mustafa Mustafa (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2022)
This paper aims to determine how the influence of leadership style on the performance of the cooperative employees of PT. Bosowa Maros Cement. This study uses quantitative analysis methods, the population in this study are employees of the cooperative PT. Bosowa Maros Cement. The number of samples used as respondents in this study were 36 respondents. Based on the results of the calculation of the correlation coefficient, obtained by 0.56. By looking at the results and the guideline table for the interpretation of the correlation coefficient, it can be concluded that there is a fairly good relationship between leadership style and the performance of the cooperative employees of PT. Semen Bosowa Maros, because it is in the correlation coefficient interval of 0.40-0.599 (good enough) which is 0.56. The calculation of the coefficient of determination shows that the influence of leadership style on the performance of the cooperative employees of PT. Semen Bosowa Maros by 31%. While 69% is influenced by other factors not examined in this study. Based on the calculation of the t test, it gets a value of 10,408. While the t table is 3.601. Because t count is greater than t table. Then the leadership style (X) has a significant effect on the performance of the cooperative employees of PT. Bosowa Maros Cement